Biosensors: Boron Doped ZIF‐67@Graphene Derived Carbon Electrocatalyst for Highly Efficient Enzyme‐Free Hydrogen Peroxide Biosensor (Adv. Mater. Technol. 12/2017). Issue 12 (12th December 2017) - Li, Zehui; Wang, Wenbo; Cao, Hongbin; Zhang, Qiang; Zhou, Xinyuan; Wang, Dongbin; Wang, Yaling; Zhang, Shuangshuang; Zhang, Guangjin; Liu, Chenming; Zhang, Yi; Liu, Rongji; et al.
Abstract : In article number1700224, Guangjin Zhang, Chenming Liu, Rongji Liu, Jingkun Jiang, and co‐workers report a enzyme‐free hydrogen peroxide biosensor based on sensitive sandwich‐like boron doped porous carbon nanomaterial. The corresponding electronic biosensor device is developed by using technologies of screen printing electrodes, integrated circuits, 3D‐printed shell, and a custom‐developed procedure. It shows excellent performance toward detection of hydrogen peroxide.